Analisis Tingkat Pendidikan, Pengalaman, dan Pelatihan Terhadap Profesionalisme Guru (Studi Kasus Pada SMK TI Bali Global Denpasar) - Learen Jatiya Masyam Putra; Nurhidayah Nurhidayah; Mohamad Rizal (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to analyze the influence of education level, teaching experience, and training on teacher professionalism at SMK TI Bali Global Denpasar. The research background is based on the demand for improving the quality of learning in technology-based vocational schools, which require teachers to have high competencies and the ability to adapt to current developments. The study employed an explanatory research design and a quantitative methodology. In this research, 36 educators made up the population and were selected using a saturation sampling approach. Using multiple linear regression after passing reliability, validity, and classical assumption tests, data were retrieved from a Likert-scale questionnaire. The results showed that simultaneously, education level, experience, and training significantly influenced teacher professionalism. Partially, experience and training proved to have a positive and significant effect, while education level showed no significant effect. The coefficient of determination value of 93.8% indicates that teacher professionalism is strongly influenced by these three variables. This finding indicates that teaching experience and ongoing training are dominant factors in shaping teacher professionalism in the era of technology- based education. Keywords : Education Level, Teaching Experience, Training, Teacher Professionalism